Desain Konfigurasi Ruang Permukiman Cikoang Berbasis Desa Wisata - Hartawan Madeali Gurawa; Victor. S; Triyatni. M; Rahmi Amin; Nurul Najdmi; Edward Syarif; Abdul Mufti; Andi Karina; Muh Yogi R (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Tourism is the main sector to generate the development. This tourism activity will be the lead of driving the regional to improve the economic sector in some area, especially for the areas that have unique potential and scarce resources. The criteria for ownership of potential uniqueness and rarity can be found in Cikoang Village, Mangarabombang District, Takalar Regency. The combination of the atmosphere of the river estuary with the natural beauty of the environment wrapped in a comfortable air temperature supported by the annual ritual of Maudu Lompoa and the catch of fresh fish from fishermen is a tourism potential that is hard to forget for travelers with high taste. Conditions like this certainly deserve to be shared with all people who love tourism. This potential is unfortunate because the environment has shown signs of deteriorating environmental quality and lack of supporting facilities to help show its superiority. The decline in environmental quality and lack of supporting facilities are the problems of this dedication. Meanwhile, efforts to bring out the golden potential of riverbank estuary village tourism are the goal of dedication. The method used to solve the problem is an architectural description approach with the consideration of the unity between elements of culture, tourism, education and culinary. The results of the study promote architectural idea of ​​an integrated regional spatial plan between cultural, educational and recreational activities. Completion of the watershed area of ​​the estuary with erosion protection construction as a tourist spot is a combine value added solution. Increasing the salt pond tourism area as a combination of tourism and education. Increasing the Maudu Lompoa cultural tourism area as a combination of cultural tourism.